2010
DOI: 10.1002/mrm.22438
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of young children to the MRI scanner environment

Abstract: Seventy children aged 2 to 7 years were exposed to the MRI environment through a series of steps typical of a research study. Their willingness to proceed through the process was used to estimate the prevalence of fear. Thirty-seven children (53%; 95% confidence interval [41%, 65%]) completed the approach sequence. Although the correlation of child age in months (Mean (M) 5 60.1, standard deviation 5 16.5, N 5 70) and highest successful step (M 5 5.8, standard deviation 5 2.6, 95% confidence interval [5.2, 6.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…Eventually, the participant accepted the syringe filled only with medication in his mouth. For Study 1, we used the successive steps to approach a mock scanner proposed by Malisza et al () to design a stimulus fading sequence with increasing duration and proximity toward the scanner. If instruction presentation and exposure to each of the steps did not result in compliance, we initiated an intervention procedure composed of prompting and contingent reinforcement.…”
Section: Study 1: Stimulus Fading Prompting and Contingent Reinforcmentioning
confidence: 99%
See 2 more Smart Citations
“…Eventually, the participant accepted the syringe filled only with medication in his mouth. For Study 1, we used the successive steps to approach a mock scanner proposed by Malisza et al () to design a stimulus fading sequence with increasing duration and proximity toward the scanner. If instruction presentation and exposure to each of the steps did not result in compliance, we initiated an intervention procedure composed of prompting and contingent reinforcement.…”
Section: Study 1: Stimulus Fading Prompting and Contingent Reinforcmentioning
confidence: 99%
“…Muehlhan, Lueken, Wittchen, and Kirschbaum () found physiological evidence of fear and stress in the form of high thalamic activity and high levels of salivary alpha‐amylase and cortisol among 13% of 39 adults undergoing an fMRI experiment. Finally, according to Malisza et al (), up to 50% of children ( n = 70) showed signs of escape and avoidance during a protocol of gradual approximation to a mock scanner. These signs included high self‐reported ratings in a fear visual analogue scale along with refusal to continue with the gradual approximation routine.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…10,11 Finally, in pediatric imaging especially, the possibility of increased subject motion makes obtaining accurate and reproducible DTI parameter values difficult. 12,13 Artifact-reducing techniques can be used to overcome some of these issues. However, particularly in pediatric imaging, these techniques are not without challenges.…”
mentioning
confidence: 99%
“…However, they often increase the acquisition time. Sedation to reduce motion artifacts is also not particularly ideal in the pediatric population [3,9,10]. Therefore, reliably fast, high-resolution DTI of the pediatric CSC is required, and various techniques of DTI have been investigated in children [3][4][5][6]11].…”
Section: Introductionmentioning
confidence: 99%